The chances of successful recruitment of volunteers among management students (in the light of empirical research) = Szanse na skuteczną rekrutację wolontariuszy wśród studentów kierunków menedżerskich (w świetle badań empirycznych) - Stankiewicz, Janina; Bortnowska, Hanna; Seiler, Bartosz (Zielona Góra: Faculty of Economics and Management Press)
Non-profit organizations pursue social objectives. They base on the work of volunteers - people who devote their time to help others without expecting in return material benefits. They can perform various works, including those ones which require knowledge and skills in the area of management. It is possible to find such competences among the students of Management. The aim of the article is to discuss some opportunities of recruitment volunteers among that target market.
Keywords: organizacje non profit; wolontariusze; rekrutacja; studenci kierunków menedżerskich; non-profit organizations; volunteers; recruitment; management students